Aplikasi Ergonomi untuk Meningkatkan Produktivitas Pengrajin Kayu Bekas (Drifwoods) di Kabupaten Badung, Bali - I Gede Nyoman Suta Waisnawa; I Made Sudana; Ida Bagus Swaputra (Universitas Negeri Makassar, 2019)
The results of the implementation of ergonomics in deco and shop camps were specifically focused onimproving work facilities, workplaces, layouts, work procedures, and work environment, increasing workers'comfort in conducting production activities, and utilizing space so that the production process becomes safe andflexible. Outputs that have been achieved included (1) workstations arranged in an efficient material flow layoutsupported by adequate work tools so it can optimize the achievement of production targets, (2) improvement of theprocess and procedures for completing work, (3) improvement and savings in the use of materials, machinery/tools,and humans, (4) utilization of humans’ efforts, (5) improving workspace arrangements that can provide acomfortable and safe working environment. The implementation of participatory ergonomics production capacitycan reach 456 pieces/year and shop production as many as 24 pieces/year, for example; tiger, bear, eagle, cow headetc. After the ergonomic intervention, the production capacity increased to 52 pieces/year. The impact of thisprogram was an increase in production capacity of Ari deco craftsmen (67.5%) and Kubu shop craftsmen (46.15%),while business partners' turnover was around 69.9%.